2022
DOI: 10.1002/jia2.25910
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of HIV status disclosure to adolescents living with HIV in Eastern Cape, South Africa: a prospective cohort study

Abstract: Introduction The World Health Organization recommends full disclosure of HIV‐positive status to adolescents who acquired HIV perinatally (APHIV) by age 12. However, even among adolescents (aged 10–19) already on antiretroviral therapy (ART), disclosure rates are low. Caregivers often report the child being too young and fear of disclosure worsening adolescents’ mental health as reasons for non‐disclosure. We aimed to identify the predictors of disclosure and the association of disclosure with adhe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The studies were conducted in five countries in Sub-Saharan Africa, namely: five studies from Ethiopia [ 45 , 46 , 48 , 49 , 55 ], two studies from South Africa [ 47 , 56 ], two studies from Uganda [ 52 , 57 ], one study from Kenya [ 50 ], one study from Namibia [ 54 ], and one multi-country (Burundi, Democratic Republic of Congo, and Cameroon) [ 53 ]. In terms of design nine studies were cross-sectional [ 45 – 50 , 52 , 54 , 57 ], one case-control [ 55 ], and two cohort [ 53 , 56 ]. Seven of the studies provided adjusted effect estimates [ 45 , 47 – 49 , 53 , 55 , 56 ], and others reported (or the authors of this meta-analysis calculated) crude estimates [ 46 , 50 , 52 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were conducted in five countries in Sub-Saharan Africa, namely: five studies from Ethiopia [ 45 , 46 , 48 , 49 , 55 ], two studies from South Africa [ 47 , 56 ], two studies from Uganda [ 52 , 57 ], one study from Kenya [ 50 ], one study from Namibia [ 54 ], and one multi-country (Burundi, Democratic Republic of Congo, and Cameroon) [ 53 ]. In terms of design nine studies were cross-sectional [ 45 – 50 , 52 , 54 , 57 ], one case-control [ 55 ], and two cohort [ 53 , 56 ]. Seven of the studies provided adjusted effect estimates [ 45 , 47 – 49 , 53 , 55 , 56 ], and others reported (or the authors of this meta-analysis calculated) crude estimates [ 46 , 50 , 52 , 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of design nine studies were cross-sectional [ 45 – 50 , 52 , 54 , 57 ], one case-control [ 55 ], and two cohort [ 53 , 56 ]. Seven of the studies provided adjusted effect estimates [ 45 , 47 – 49 , 53 , 55 , 56 ], and others reported (or the authors of this meta-analysis calculated) crude estimates [ 46 , 50 , 52 , 54 , 57 ]. In studies that reported adjusted estimates [ 45 , 47 – 49 , 53 , 55 , 56 ], the factors controlled for include age (both caregiver and child), caregiver’s sex, country, education and school type, knowledge and attitude towards ART medication, motivation for medication, regimen type, caregiver’s substance use, family income, viral load change, child medication burden, distance travelled, and orphan hood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 There was no significant association between knowledge of HIV status and the categorization into 4 adherence trajectories. This may be partly explained by the fact that the majority of adolescents already knew their HIV status at baseline 36 and the potential confounding effects of age at ART initiation and the duration of ART 48 or that the disclosure process or pattern may influence adherence more than knowledge of status. 49 The heterogeneity observed in the adherence trajectories among ALHIV in this study is very relevant to improving their HIV-related health outcomes, given that it is highly associated with VL outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected on sociodemographic characteristics, including age (divided into 10–14 and ≥15 year age groups), sex, urban/rural residence, and access to 8 socially perceived necessities for children and adolescents validated in a nationally representative South African Social Survey (eg, enough food). 35 HIV treatment factors included knowledge of HIV status, 36 estimated or self-reported time on ART (years), and mode of HIV acquisition. Mode of HIV acquisition (perinatally versus sexually acquired HIV) was defined following existing sub-Saharan African pediatric cohorts: age of ART initiation cutoff [≤10 years] 37 validated and updated with a detailed algorithm that considered other strong evidence (ie, self-reported sexual history and parental death) in the absence of definitive clinic notes ascribing mode of HIV acquisition.…”
Section: Methodsmentioning
confidence: 99%